Ocular ultrasonography and ultrasound biomicroscopy: applicability in clinical and ophthalmic surgery - Merlini, Natalie Bertelis [UNESP]; Souza, Livia Pasini de [UNESP]; Bortolini, Zara [UNESP]; Sartor, Raquel [UNESP]; Brandão, Claudia Valeria Seullner [UNESP]; Ranzani, José Joaquim Titton [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Univ Federal Rural Pernambuco, 2011)
With the advent of high frequency transducers, the use of ocular ultrasound has become widely used because it provides definitions of major ocular structures. This diagnostic tool is useful in the evaluation of ophthalmic injuries, and also used for qualitative and quantitative evaluation of intraocular and orbital lesions. It is a noninvasive, safe and fast, easy to use and can be performed in an awake animal. The ocular ultrasonography is indicated in cases of ocular opacity, when the ophthalmic examination cannot be done, and in eyes with ocular trauma or suspected orbital disease. Ultrasound biomicroscopy (UBM) is a diagnostic tool with high cost and sedation or general anesthesia is necessary, but has the advantage of evaluating structures poorly defined or visualized in the anterior segment of the eye. Therefore, this paper aims to show the importance of ocular ultrasonography and UBM to veterinary practitioners, and to demonstrate its advantages and indications in ophthalmic routine.
Keywords: Eye ultrasound; Ultrasound biomicroscopy